Prevalence, incidence, and Disability-Adjusted Life Years of self-harm and suicide mortality in the Middle East and North Africa: a sex-specific study based on Global Burden of Disease - Khan, Moien AB; Amiri, Sohrab (Frontiers in Psychiatry, 2025)
ObjectivesThe study examined the prevalence, incidence, and Disability-Adjusted Life Years (DALYs) associated with self-harm across countries in the Middle East and North Africa, while also analyzing suicide mortality. It aims to explore the variations in self-harm and suicide mortality by sex and assess trends in these phenomena from 1990 to 2021.MethodsGlobal Burden of Disease 2021 data sources were used in this study. Estimates for all-age counts and age-standardized prevalence rates (per 100,000) were determined for prevalence, incidence, Disability-Adjusted Life Years (DALYs), and suicide mortality. These disease burden indicators were analyzed across the period from 1990 to 2021, and the results were further stratified by sex and location. Additionally, the percentage change observed between 1990 and 2021 was documented. A 95% uncertainty interval was used for each estimate reported.ResultsThe age-standardized prevalence of self-harm in the MENA region was 111.82 per 100,000 in 1990, decreasing to 105.84 by 2021. The global age-standardized prevalence rate of self-harm is 182.24 per 100,000 in 2021. Throughout this period, the self-harm rates in the MENA region remained lower than the global average. In 2021, approximately 621,509 individuals in the region were reported to engage in self-harm. In the same year, the age-standardized suicide mortality rate in MENA stood at 3.43 per 100,000, with an estimated total of over 21,000 suicide deaths. The age-standardized DALYs rate of self-harm in MENA was 246.03 per 100,000 in 1990 and decrease to 177.44 per 100,000 in 2021. The gender disparity in 2021 revealed higher self-harm rates among females than males, at 112.57 vs. 99.67 per 100,000, respectively. In contrast, suicide mortality rates were higher in males than females, recorded at 4.83 vs. 1.92 per 100,000.ConclusionsAlthough the rates of suicide mortality and self-harm have declined, the overall number of cases has risen alongside population growth. This highlights the necessity for more comprehensive efforts in mental health care, including screening, prevention, treatment, and the accurate identification of risk factors.